Pendugaan Erosi Aktual Berdasarkan Metode USLE Melalui Pendekatan Vegetasi, Kemiringan Lereng dan Erodibilitas di Hulu Sub DAS Padang - Imam Bukhari; Kemala Sari Lubis; Alida Lubis (Jurnal Agroekoteknologi, 2015)
Erosion strongly influenced by vegetation, slope and erodibility. USLE method used to predictactual erosion. Vegetation factor, slope and erodibility used to examine the relationship of the actualerosion and analyzed with multivariate. Soil sampling in the upstream Sub DAS Padang at Rayadistrict, Simalungun based on vegetation, slope and erodibility with a sample size of the 33 samplepoints. The results showed that the highest erosion at 7.177,84 tons.ha-1.year-1 on the non-vegetationwith criteria levels classified as very severe erosion hazard and lowest erosion of 24,30 tons.ha-1.year-1 on the forest vegetation protected by the criteria of erosion potential as very mild.Keywords : Soil erosion, USLE method, DAS Padang